1996
DOI: 10.1159/000179189
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-ll-lnduced Angiogenesis in Sponge Implants in Mice

Abstract: Stimulators of angiogenesis hold potential in promoting the development of collateral circulation in ischaemic tissue and accelerating wound healing, but promote pathological vasoformation in angiogenesis-dependent diseases (solid tumours, atherosclerosis). The renin-angiotensin system is implicated in both beneficial angiogenesis and pathological vascular growth. We investigated the angiogenic activity of angiotensin II (All) in a sponge implant model in mice; this peptide enhanced angiogenesis, as well as gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…13,20 Arteriosclerotic lesions exhibit increased formation of microvessels within the adventitia and the hyperplastic media. Therefore, we examined protein expression of ACE, Ang II, and CYR61 within capillaries and small blood vessels in lesion areas.…”
Section: Colocalization Of Ang II and Cyr61 In Microvessels Of Human mentioning
confidence: 99%
“…13,20 Arteriosclerotic lesions exhibit increased formation of microvessels within the adventitia and the hyperplastic media. Therefore, we examined protein expression of ACE, Ang II, and CYR61 within capillaries and small blood vessels in lesion areas.…”
Section: Colocalization Of Ang II and Cyr61 In Microvessels Of Human mentioning
confidence: 99%
“…[10][11][12][13] Other studies have also investigated the angiogenic effects of exogenous AII in vivo angiogenesis models. [14][15][16][17] Furthermore, recent studies have revealed local expression of several components of the RAS in various cancer cells and tissues. 18 A large-scale clinical trial for hypertension demonstrated that inhibitors of angiotensin-converting enzyme (ACE) reduced mortality rates not only of those due to cardiovascular diseases but also those due to malignant tumors.…”
mentioning
confidence: 99%
“…Angiotensin II (Ang II), a major participant in the RAAS, was initially described as a vasoconstrictor, but recent studies have revealed that it also participates in cell growth, cell differentiation and apoptosis (Stoll et al, 1995;Escobar et al, 2004), and has a role in cell migration and conformation of the extracellular matrix (Coker et al, 2001). Some reports indicate that Ang II induce neovascularisation (Fernandez et al, 1985;Le Noble et al, 1991;Andrade et al, 1996) due to stimulation of growth factors, such as platelet-derived growth factor (PDGF) (Khachigian et al, 2000;Cook et al, 2002), transforming growth factor beta b (TGFb) (Kagami et al, 1994;Ohta et al, 1994;Hamaguchi et al, 1999;Weigert et al, 2002), insulin-like growth factor 1 (IGF-1) (Brink et al, 1999;Haddad et al, 2003), basic fibroblast growth factor (bFGF) (Peng et al, 2001), vascular endothelial growth factor (VEGF) (Otani et al, 1998;Tamarat et al, 2002) and angiopoietin 2 (Otani et al, 2001). Angiotensin II also induces the expression of proto-oncogenes in smooth vascular muscle cells, including c-fos, c-jun, c-myc, erg-1, VL-30, and the activator of the protein 1 complex (Cook et al, 2002), Interestingly, many of these effects are inhibited by the blockage of the AT 1 receptor (Fujiyama et al, 2001).…”
mentioning
confidence: 99%